IMPLEMENTASI UU SP3K PADA KELEMBAGAAN PENYULUHAN PERTANIAN DI KOTA PEKANBARU - ARIFUDIN ARIFUDIN; ERI SAYAMAR; SUSY EDWINA; WAHYUNI RIZKI (Universitas Sebelas Maret, 2021)
This study aims to probe the implementation of agricultural extension in Pekanbaru City according to articles 13, 14, and 15 Act Number 16 year 2006 upon the Extension System of Agriculture Fisheries and Forestry (Act SP3K). The research method was executed through the survey where the purposive sampling as the data collection system, which semistructured interviews with the 30 respondents was conducted, with the detail 15 people from the Counseling Executing Agency of Pekanbaru and 15 extensionists from the three Technical Units of Agricultural Extension Agency (UPTB PP) District of Pekanbaru.